A comparative study of spatiotemporal patterns of urban expansion in six major cities of the Yangtze River Delta from 1980 to 2015. Issue 4 (3rd April 2018) - Fang, Chenyu; Zhao, Shuqing
ABSTRACT: Introduction: China has been experiencing dramatic urbanization in parallel with its economic boom over the past three to four decades. The Yangtze River Delta (YRD), as the most important engine in the Chinese economy, has pioneered in the rapid urbanization road of China since the late 1970s. We quantified and compared the spatiotemporal patterns of urban expansion in six major cities in the YRD urban agglomeration between 1980 and 2015. Outcomes: We found that Shanghai, Nanjing, Hangzhou, Wuxi, Suzhou and Ningbo expanded by an annual rate of 5.4%, 5.9%, 9.6%, 7.4%, 6.3% and 8.1% from 1980 to 2015, suggesting larger cities generally possess lower growth rates. Spatiotemporal patterns of urban expansion are defined by multiple forces including physical conditions and urban planning and policy. The urbanization processes in Shanghai, Nanjing and Hangzhou generally conformed with the diffusion-coalescence theory as the number of patches (NP) and patch density (PD) of urbanized land peaked and the proportion of leapfrogging urban growth type began to decrease around 2005, which separating their urbanization processes into diffusion phase before and coalescence phase after. In contrast, Suzhou, Wuxi and Ningbo is either in the diffusion or in the transition phase from diffusion to coalescence, not showing temporal dynamics of diffusion-coalescence phase across the study period, which might be related to the fact that the urban areas in these three cities were more dispersive in space than that of other cities. Conclusions: These spatially explicit findings are the fundamental cornerstone to understand the characteristics, drivers and consequences of urban expansion in the urban agglomerations, and then detect the feasibility of general urbanization theories and further advance in-depth theoretical understanding to support a sustainable urban future.